The work stress, occupational burnout, coping strategies and organizational support of elite sports coaches in Sichuan Province: the mediating role of organizational support - Yu, L.; Cheng, L. (Frontiers in Psychology, 2024)
Objective: This study investigated the relationships between job pressure, occupational burnout, organizational support and coping strategies among competitive sports coaches in Sichuan Province, China. It also assesses the impact of job pressure on occupational burnout and the mediating roles of organizational support and coping strategies.